KETERTARIKAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU TERHADAP PEMBELAJARAN SASTRA JEPANG - Pertiwi, Tiara; Isnaini, Zuli Laili; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to analyze the level of interest among students inthe Japanese Language Education Program (PSPBJ) at the Faculty of TeacherTraining and Education (FKIP) University of Riau towards learning Japaneseliterature in the odd semester of the 2023/2024 academic year. The research methodused is descriptive quantitative, with data collection conducted through a Likert-scale-based questionnaire. The results of the study indicate that student interest inlearning Japanese literature is categorized as very high, with a percentage of76.02%. Factors contributing to this high level of interest include enthusiasm forlecture materials, interest in Japanese literature and culture, participation inactivities related to Japanese literary works, and a desire to follow thedevelopments of favorite artists or writers. The implications of this research can beused to optimize the PSPBJ curriculum at Universitas Riau to enhance studentinterest and participation in learning Japanese literature. Recommendations forfuture research include expanding the number of respondents, conducting long-termstudies to monitor changes in student interest, and developing more in-depthresearch instruments.Keywords: Japanese Literature, Interest, Education, Enthusiasm